VICINE AND CONVICINE LEVELS IN DRY AND FRESH BEANS DURING THE GROWTH STAGES AND THE EFFECT OF ENZYMATIC TREATMENT AND PROCESSING CONDITIONS ON THEIR REMOVAL. - H. K. Ali; K. A. Shakir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Beans (Vicia faba) contain some anti-nutritional compounds, especially vicine and convicine and their non-sugar derivatives, divicine and isouramil, which are responsible for the occurrence of Favism in people with hereditary deficiency of Glucose-6-phosphate dehydrogenase (G6PD). These study objective was estimation of vicine and convicine content and their distribution in dry and green bean parts during the growth stages, and the effect of beta-glucosidase from defatted apricot seed powder and some home-based processing conditions on elimination of these compounds from the bean. The results showed that the content of vicine & convicine in bean ranged from 22.7 mg/100 g in the seedling stage to 46.8 mg/100 g in the pods stage at 139 days. As for vicine, it ranged from 12.6 mg /100g to 29 mg/100g at the above stages respectively. While for convicine it ranged from 10.1 mg/100g to 17.8 mg/100 respectively. The enzymatic treatments showed significant elimination of those compounds as compared to non-enzymatic treatments. Additionally, other factors such as soaking temperature, pH, and time as well as cooking process had a positive effect on the elimination of those glucosides.